(3VhA GdSGQi HeYQaI NHQ Jeje GdOGQis - (3Jbj GdOjf CMeO Hf Ydj Hf YHO GdbGOQ GdebQjRj GdeUQj,J (B854 (3g` s ((3KZQ LOI s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg hHYO agPg ebGdI hLjRI SejJgG GdVhA GdSGQi HeYQaI NHQ Jeje GdOGQi aUd (B: (3GJab LejY aQb GdESdGe Ydi Cf fSe LejY GdCfS Ydi GNJdGa CLfGSge eNdhbg ef BOe Ydjg GdSdGe s
(3BNQgG (B:s
(3ef GdOGQjjf Zdi Cf GSJQOgG GdeSdehf afMJGL Edi cja hVY ef YGO efge Edi GdHdGO gPg HWQjb TQYi COe hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B141 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs